Kin Altruism, Psychological Contract and Commitment in Immigrant Businesses: Some Theoretical Propositions - Yang, Chulguen Charlie (QRBD, 2014)
Keywords: dept.mgt; peer-reviewed

Gender differences in the endowment effect: Women pay less, but won’t accept less - Wieland, Alice; Sundali, James; Kemmelmeier, Markus; Sarin, Rakesh (Judgment and Decision Making, 2014)
We explore different contexts and mechanisms that might promote or alleviate the gender effect in risk aversion. Our main result is that we do not find gender differences in risk aversion when the choice is framed as a willingness-to-accept (WTA) task. When the choice is framed as a willingness-to-pay (WTP) task, men are willing to pay more and thus exhibit lower risk aversion. However, when the choice is framed as a willingness to accept task, women will not accept less than men. These findings imply gender differences in the endowment effect. We also find that the effect size of the gender difference in risk aversion is reduced or eliminated as the context changes from tasks framed as gambles to other domains; and that attitudes toward gambling mediate the gender effect in gambling framed tasks.
Keywords: dept.mgt; endowment effect; gambling attitudes; gender; peer-reviewed; risk attitudes; risk aversion; sex differences

Knowledge management and organizational performance in the service industry: The role of transformational leadership beyond the effects of transactional leadership - Birasnav, M. (Journal of Business Research, 2014)
This study examines a comprehensive model comprising of various relationships between transformational and transactional leadership, knowledge management (KM) process, and organizational performance. Data are collected from human resource managers and general managers working in 119 service firms. Exploratory factor analysis and hierarchical regression analysis are used to analyze the proposed hypotheses. The results indicate that transformational leadership has strong and positive effects on KM process and organizational performance after controlling for the effects of transactional leadership. Further, KM process partially mediates the relationship between transformational leadership and organizational performance after controlling for the effects of transactional leadership. Implications and directions for future research are also discussed.
Keywords: Knowledge management; Organizational performance; Transactional leadership; Transformational leadership; dept.mgt

AACSB accreditation and possible unintended consequences: A deming view. - Stepanovich, Paul L; Mueller, James; Benson, Dan (The Journal of Education for Business, 2014)
The AACSB accreditation process reflects basic quality principles, providing standards and a process for feedback for continuous improvement. However, implementation can lead to unintended negative consequences. The literature shows that while institutionalism and critical theory have been used as a theoretical base for evaluating accreditation, W. E. Deming's philosophy has not. This article fills that void by examining possible negative consequences in meeting faculty qualification requirements in institutions with a teaching mission. © 2014, Copyright Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-359-118-710-616 tex.type: [object Object]
Keywords: AACSB accreditation; Deming; dept.mgt; profound knowledge

Gossip in organizations: from an evolutionary psychological perspective - Yang, Chulguen; Minjock, Robert; Voss, Bernard Edward; Colarelli, Stephen M (Academy of Management Proceedings, 2014)
Gossip is often portrayed as a trivial and even destructive behavior at work. This paper integrates previous studies on gossip using a multilevel evolutionary framework and proposes a few empirical propositions to develop a more balanced view on gossip as a medium of informal communication in organizations.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/079-776-281-946-710
Keywords: Evolutionary framework; Informal communication; dept.mgt